2021
DOI: 10.1002/bem.22343
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Frequency Pulsed Magnetic Field Reduces Neuropathic Pain by Regulating NaV1.8 and NaV1.9 Sodium Channels at the Transcriptional Level in Diabetic Rats

Abstract: Low-frequency pulsed magnetic field (LF-PMF) application is a non-invasive, easy, and inexpensive treatment method in pain management. However, the molecular mechanism underlying the effect of LF-PMF on pain is not fully understood. Considering the obvious dysregulations of gene expression observed in certain types of voltage-gated sodium channels (VGSCs) in pain conditions, the present study tested the hypothesis that LF-PMF shows its pain-relieving effect by regulating genes that code VGSCs proteins. Five ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…However, the decrease in inflammatory cytokines as well as the proangiogenic effect contribute to the anti-edema effects [31]. The neuro-modulatory activity is mainly related to ion channels modulation (especially sodium, potassium, and calcium channels) [32][33][34], but also to a neuroprotective effect associated with the brain-derived neurotrophic factor (BDNF) increase [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the decrease in inflammatory cytokines as well as the proangiogenic effect contribute to the anti-edema effects [31]. The neuro-modulatory activity is mainly related to ion channels modulation (especially sodium, potassium, and calcium channels) [32][33][34], but also to a neuroprotective effect associated with the brain-derived neurotrophic factor (BDNF) increase [35].…”
Section: Discussionmentioning
confidence: 99%
“…An animal model by Coksun et al showed that low-frequency PEMFs are capable to modulate ionic channels in rats. Sodium channels NaV 1.8 and NaV 1.9 , down-regulated in painful conditions, were re-regulated after PEMF treatment [ 55 ]. In an in vitro study by Ahmed et al, the action of PEMFs on depolarization and sodium/potassium channels was described [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A parallel sham-treated group showed no significant improvement. A slightly different PEMF pattern, consisting of pulse trains of 1.5 mT peak delivered at 10-Hz or 30-Hz, was used to assess neuropathy pain mitigation and biomarkers of PEMFT changes [ 31 ]. Both patterns improved allodynia and hyperalgesia measures, with the 10-Hz pattern being more effective and sham treatment producing no improvement.…”
Section: Reviewmentioning
confidence: 99%